Design and Field Tuning of an Upstream Controlled Canal Network SCADA - Rijo, Manuel (2012)
ABSTRACT The paper presents the design, implementation and field tuning of a supervisory and control system of an irrigation canal network upstream controlled with AMIL radial gates and equipped with other Neyrpic devices such as automatic siphons and orifice modules. Besides the hydraulic system, the paper also presents the supervisory and control system architecture, including a few synoptics, and their remote terminal units (monitoring or control and monitoring units). The developed and field tuned manual and automatic controllers are also presented. The manual controllers – direct and gate position controllers (for the gates operation) and gate flow controllers - are defined for the main canals and main distributors intakes in order to permit a pre-defined flow value or a daily flow schedule achievement and also defined for a few gate controlled bottom canal orifices used to discharge the overflow to the drainage system. The automatic controllers - water depth controllers for a few gate controlled bottom canal orifices – are defined in order to prevent automatically canal overtopping. The supervisory and control system also monitor the outflows at the main canals and the main distributors - the most important canal top side weirs, canal terminal weirs and automatic Neyrpic siphons. The flow equations used in the computing of flow in real-time inside the developed controllers and the monitoring units were field tuned using collected data readings from a monostatic doppler current meter. The tuning parameters are also defined and presented.